How does Bt cotton perform in rainfed areas? - A Narayanamoorthy; C Renuka; K S Sujitha (Agricultural Economics Research Review, 2023)
Bacillus thuringiensis (Bt) cotton is the only genetically modified crop permitted for commercial cultivation in India. We use farm-level data from 150 sample farmers cultivating cotton in rainfed areas in Tamil Nadu, a state in India, and conduct multiple regression analysis to compare its economic performance with that of non-Bt cotton. Compared to non-Bt cotton cultivated in a similar environment, Bt cotton reduces pesticide consumption by about 28%. Since Bt cotton is resistant to bollworm infestation, productivity is higher by 34% and profitability by 98%.